2017
DOI: 10.1021/acsami.6b16669
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Doxorubicin-Conjugated Gold Nanoparticles: Regulation of Drug Location

Abstract: Drug-conjugated gold nanoparticles (GNPs), which are generally constructed with many molecules of thiol-terminated polyethylene glycol (PEG)-drug decorated on their surfaces via a thiol-Au covalent bond, are promising and efficient nanoprodrugs. However, because of the exposure of the hydrophobic drug molecules on the surface of the conjugate, in vivo stability, opsonization, and subsequent inefficient therapy become the main issues of this system. To solve these problems without complicating the structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 39 publications
2
36
0
2
Order By: Relevance
“…Cui et al designed PEG-modified GNPs to deliver DOX, and the results showed that the nanomedicine had higher solubility, stability, and dispersibility. 116 In addition, GNPs have a unique two-step drug release, respectively, in the lysosome and in the cytoplasm, thus a controlled and sustained release of the drug can be achieved which in turn can improve the antitumor effect of the drugs. 116 Hamzawy et al designed to use GNPs and liposome-embedded GNPs (LGNPs) to deliver temozolomide (TMZ).…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al designed PEG-modified GNPs to deliver DOX, and the results showed that the nanomedicine had higher solubility, stability, and dispersibility. 116 In addition, GNPs have a unique two-step drug release, respectively, in the lysosome and in the cytoplasm, thus a controlled and sustained release of the drug can be achieved which in turn can improve the antitumor effect of the drugs. 116 Hamzawy et al designed to use GNPs and liposome-embedded GNPs (LGNPs) to deliver temozolomide (TMZ).…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…116 In addition, GNPs have a unique two-step drug release, respectively, in the lysosome and in the cytoplasm, thus a controlled and sustained release of the drug can be achieved which in turn can improve the antitumor effect of the drugs. 116 Hamzawy et al designed to use GNPs and liposome-embedded GNPs (LGNPs) to deliver temozolomide (TMZ). TMZ-loaded GNPs (TGNPs) and TMZ-loaded LGNPs (LTGNPs) were used against urethane-induced lung cancer in BALB/c mice through intratracheal inhalation.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Furthermore, while the nonspecific distribution of chemotherapy drugs in vivo, accompanied with rapid clearance, significantly limits the drug potency, administering drugs at higher dosage is undesirable as it often poses a serious cytotoxic threat. To overcome the conventional drawbacks of chemotherapy, a variety of drug carriers such as polymeric nanoparticles, 19 polymeric micelles, 20 dendrimers, 21 liposomes, 22 magnetic nanoparticles (MNPs), 23 and silica 24 or gold nanoparticles 25 have been used to achieve targeted drug delivery (TDD).…”
Section: Introductionmentioning
confidence: 99%
“…However, its short systemic circulation time, undesirable biodistribution, and nonspecific toxicities to cancer/normal cells lead to not only relatively low anticancer efficacy but also severe side effects [4,5]. To address these issues, various nanocarriers such as liposomes [6], micelles [7], dendrimers [8], metal-organic frameworks (MOFs) [9], carbon nanomaterials [10], and gold nanomaterials [11,12] have been designed for the efficient delivery of DOX to cancer cells. Among them, conventional nanocarriers which tend to release the encapsulated DOX molecules passively cannot realize controllable drug release and fail to achieve satisfactory therapeutic efficacy [13].…”
Section: Introductionmentioning
confidence: 99%